A case report of successful diagnosis of a pulmonary nodule by a survey of oncogenic mutations; primary lung carcinoma or pulmonary metastasis?. (2016) - Haro, Akira; Kuramitsu, Erina; Yamamoto, Ichiro; Fukuyama, Yasuro
Highlights: It is very difficult to make a differential diagnosis between primary and metastatic lung carcinoma. The NRAS mutation is detected in several tumors, but the sites and the amino changes of NRAS mutaion is various. Examination of oncogenic mutation is a useful in the diagnosis of pulmonary tumors. Abstract: Introduction: The number of patients diagnosed with solid carcinomas is increasing, and the most common site of metastasis is the lungs. It is often difficult to make a differential diagnosis between primary lung carcinoma and metastatic lung tumor in using histological examination and by determining their immunohistological status. Presentation: A 64-years-old man presented with dyspnea with chest computed tomography (CT) findings of a pulmonary tumor, and afterwards suffered from a sudden bowel hemorrhaged due to colorectal carcinoma. The histological diagnosis of a pulmonary tumor was poorly differentiated adenocarcinoma. Both Thyroid transcription factor-1 (TTF-1) and Cytokeratin20 (CK20) were immunohistologically negative. Of the some oncogenic mutations investigated, a neuroblastoma RAS viral oncogen homolog (NRAS) codon13 G13D mutation was detected in both the colorectal carcinoma and the pulmonary tumor tissue samples. Based on the result, the pulmonary tumor was diagnosed as a metastasis derived from colorectal carcinoma. Discussion: Recently, examination of the oncogenes of solid carcinomas has been clinically investigated in primary lung caricnoma and in colorectal carcinomas. The clinical advantage of the oncogenic mutation survey is to identify the site, and the type, of amino acid change in detail. This case is a rare successful case of a survey of the oncogenes for giving a differential diagnosis. Conclusion: A survey of the oncogenic genes is very useful to make a differential diagnosis between primary lung carcinoma and metastatic lung tumor.